PENGGUNAAN KIALO EDU UNTUK MENGEMBANGKAN IDE MENULIS ESAI ARGUMENTATIF : PERSEPSI MAHASISWA - Eka Fajar Rahmani (Bajang Institute, 2023)
This study aims to explore students' perceptions of the use of Kialo Edu in developing ideas for writing argumentative essays. The participants of this study were thirteen of sixth semester students of the Pontianak Foreign Language Institute who enrolled essay writing class. The methodology employed was a descriptive study with a three-scale closed questionnaire and semi-structured interviews as data collection instruments. The findings indicated that after using Kialo Edu for three times, students showed positive perceptions in developing ideas for writing argumentative essays. 5 of the 7 statements on the questionnaire received a 100%